IR 4.0 in the Construction Industry: Challenges & Opportunities - Kennedy, Ickx Baldwin (IRC, 2019)
The trend of digitisation, automation and the increase use of ICT have been envisioned as the main concept of Industry 4.0. Comparing the progressions between multiple industries, the construction industry was found to be reluctant in incorporating these innovative technologies into its common practices despite the drastic developments demonstrated by the other industries.